2014
DOI: 10.3109/08820538.2014.962162
|View full text |Cite
|
Sign up to set email alerts
|

Epiphora after Uncomplicated Phacoemulsification: Study of Prevalence and Associated Factors

Abstract: Presence of epiphora two weeks after phacoemulsification was infrequent, despite being present in a high proportion of patients before surgery. There was not a noticeable increase in epiphora at three months. The most frequently related factors were mixed disorders of the ocular surface and lacrimal system, without an important incidence of unctual and canalicular stenosis. We consider that our perception about complaints from patients after phacoemulsification may be biased due to those who had previously suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
(10 reference statements)
1
4
0
Order By: Relevance
“…The findings of our study revealed otherwise, which might imply that surgical trauma and its effects of the lacrimal drainage system may be similar in both phacoemulsification and SICS. The findings of our study are consistent with another study by Ruiz-Calvo et al, 4 who evaluated the incidence of postoperative epiphora 3 months after uncomplicated phacoemulsification. They found it to be 7% epiphora 3 months after surgery.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings of our study revealed otherwise, which might imply that surgical trauma and its effects of the lacrimal drainage system may be similar in both phacoemulsification and SICS. The findings of our study are consistent with another study by Ruiz-Calvo et al, 4 who evaluated the incidence of postoperative epiphora 3 months after uncomplicated phacoemulsification. They found it to be 7% epiphora 3 months after surgery.…”
Section: Discussionsupporting
confidence: 93%
“…Ruiz-Calvo A et al 4 conducted a study on epiphora after uncomplicated phacoemulsification after surgery and found that presence of epiphora two weeks after cataract surgery was infrequent but that there was a significant rise three months after surgery. In patients with "new onset" epiphora, the causes were blepharitis, low tear break-up time, high tear meniscus, partial nasolacrimal duct obstruction and punctal stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the frequency of cataract carriers and concomitant NLDO is quite low (6) , as participants reported that this affected <5% of their patients.Most (53.8%) Brazilian cataract surgeons reported that their preferred approach for screening of possible NLDO is lacrimal sac expression upon examination of secretion reflux. An Indian study reported that this test is routinely used for screening of lacrimal obstruction, with a sensitivity of 93.2% and specificity of 99.3% (7) .…”
Section: Discussionmentioning
confidence: 70%
“…In none of these 109 citations had the prevalence of epiphora in the adult general population been assessed as a primary end point. In only one citation, it was mentioned that out of 125 patients, 7.2 % indicated having already had epiphora before cataract extraction (when interviewed by phone 3 months after surgery) [3]. However, it is worth mentioning that two large population-based studies addressed (not in adults) the incidence of epiphora in infants and children.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, studies assessing epiphora as a symptom, based, for example, on interviews or questionnaires, could be potentially easier to conduct. In this respect, the couple of references [3,5] retrieved by the PubMed searches and quoted in the present paper were retrospective studies actually based on written questionnaires and phone interviews. The two studies found on adults [3,6] that mentioned a prevalence of epiphora between 7.2 and 32 % are certainly informative, but these observations deserve to be confirmed by additional investigations.…”
Section: Discussionmentioning
confidence: 99%